Catalytic ammonia decomposition to COx-free hydrogen over ruthenium catalyst supported on alkali silicates. (15th October 2022) - Zhiqiang, Fu; Ziqing, Wang; Dexing, Li; Jianxin, Lin; Lingzhi, Yu; Qin, Wu; Zhong, Wei
Graphical abstract: Highlights: The oxygen vacancies (Vo) would appear in Ru/Ru/A2 SiO3 (A=Li, Na and K) after H2 reduction. The formation Vo would induce the production of EMSI effect and higher Ru dispersion. A2 SiO3 (A=Li, Na and K) can transfer their electron to Ru particle through EMSI effect. K2 SiO3 is firstly reported to be an effective support as Ru catalyst for NH3 decomposition. Abstract: A series of alkali metal silicates A2 SiO3 (A = Li, Na and K) were synthesized by a sol–gel method route and employed as support for Ru nanoparticles to catalyze NH3 decomposition. The NH3 conversion can be ranked as the order of Ru/K2 SiO3  > Ru/Na2 SiO3  > Ru/Li2 SiO3  > Ru/SiO2 at the same conditions, and Ru/K2 SiO3 displays the highest NH3 conversion of 60.5% with the TOF H2 of 2.03  s −1 under the weight hourly space velocity (GHSV) of 30, 000 mL.gcat -1 .h −1 at 450 o C. The combination results of different characterization indicate that the formation of alkali metal silicates can increase the strength and number of basic sites, and the strong electronic metal-support interaction (EMSI) would appear between Ru particles and oxygen vacancies in A2 SiO3 structure at reduction conditions. The presence of EMSI can result in the higher Ru dispersion and enhanced electronic density of Ru particles over A2 SiO3, greatly facilitating the decomposition of NH3 to COx -free hydrogen.